Regards homoérotiques étrusques : une archéologie impossible ? - Sophie Pérard (Images Re-Vues)
The aim of this paper is to put into perspective the sources concerning homoerotic relationships in Etruscan culture, by attempting to restore the Etruscans' own gaze of this type of interaction. It is important to underline the relative small amount of data at hand, which in itself is a question: it is mainly composed of images, given the specificity of the Etruscan case, for which we do not have direct literary sources and of which epigraphic sources are difficult to interpret. However, if homoerotic relationships are well known in Hellenic culture, especially in a male context, what can we say about them in Etruscan culture? Moreover, in this highly institutionalized field because it is part of paideia, the Etruscans may not have merely adopted Greek models but have rather created discourses and images in accordance with their cosmology.